Über die Sequenzanalyse an Ribonukleinsäuren - Martin A. Billeter (CHIMIA)
Methods used for the nucleotide sequence determination of ribonucleic acids are reviewed. Special emphasis is given to a new approach to the sequence determination of bacteriophage Qß RNA using enzymatically synthesized RNA.